Computer Simulation of Solution/Electrode Interfaces - Fernandes,Fernando M.S. Silva (2008)
This article is based on the plenary lecture that I was invited to present in the XIV Encontro da Sociedade Portuguesa de Electroquímica and X Iberic Meeting of Electrochemistry, a meeting which was a tribute to the late Professor César Viana. The best way I found to honour his memory was to review the highlights of a recent investigation on the computer simulation of solution/electrode interfaces carried out at our molecular simulation group, which would never happen without the enthusiasm and support of Prof. César Viana. In this paper we focus on the determination, from first principles, of the interaction potentials between ethanol and gold surfaces aiming at their use in the computer simulation of adsorption and self-assembly processes on noble metal electrodes. An analytical force field has been proposed and fitted to DFT results, by means of genetic algorithms. The force field has been tested against Monte Carlo simulations. Finally, the non-trivial, or even impossible, task of finding analytical functions that accurately match ab initio/DFT data, when many molecular degrees of freedom are involved, is briefly reviewed. The alternative of using neural networks to approach potential energy surfaces (PES) is presented and applied to the specific case of the ethanol-Au interactions. The article is signed by the persons who mainly contributed to this work. They all praised very much Prof. César Viana. It is our tribute to his memory.